1999
DOI: 10.1111/j.1600-0579.1999.tb00070.x
|View full text |Cite
|
Sign up to set email alerts
|

A survey of the computer literacy of undergraduate dental students at a University Dental School in Ireland during the academic year 1997–98

Abstract: As dental practice management becomes more computer-based, the efficient functioning of the dentist will become dependent on adequate computer literacy. A survey has been carried out into the computer literacy of a cohort of 140 undergraduate dental students at a University Dental School in Ireland (years 1-5), in the academic year 1997-98. Aspects investigated by anonymous questionnaire were: (1) keyboard skills; (2) computer skills; (3) access to computer facilities; (4) software competencies and (5) use of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
25
0

Year Published

2001
2001
2004
2004

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 2 publications
0
25
0
Order By: Relevance
“…Significant differences may be observed with regard to e‐mail use (several times a week): 62.9 psva in this survey used e‐mail: 53 psva in Wilton, Ireland, in 1998 (Ray and Hannigan, 1999), more than 54 psva in Berne in 1999 (Frey and Hofer, 1999); 93.6 psva in Finland in 2000 (Virtanen and Nieminen, 2002), about 54% of psva at the University of Illinois in 1996, rising to 84% in 1997 (Hollander, 1999). E‐mail use by medical students increased from 43% in 1991 to 100% in 2002 at the Commonwealth University in Richmond, Virginia (Seago et al, 2002).…”
Section: Discussionmentioning
confidence: 81%
See 3 more Smart Citations
“…Significant differences may be observed with regard to e‐mail use (several times a week): 62.9 psva in this survey used e‐mail: 53 psva in Wilton, Ireland, in 1998 (Ray and Hannigan, 1999), more than 54 psva in Berne in 1999 (Frey and Hofer, 1999); 93.6 psva in Finland in 2000 (Virtanen and Nieminen, 2002), about 54% of psva at the University of Illinois in 1996, rising to 84% in 1997 (Hollander, 1999). E‐mail use by medical students increased from 43% in 1991 to 100% in 2002 at the Commonwealth University in Richmond, Virginia (Seago et al, 2002).…”
Section: Discussionmentioning
confidence: 81%
“…Computer skills of medical students at the University of Chicago were reported as being 91/92% sufficient in 1996/1997 (Hollander, 1999), whereas results of a 1996 survey of British dental students show that only 77 psva assessed themselves as competent in some basic computer skills or as unable/beginners. In a survey made after a computer‐assisted learning room was opened at this university in 1997, 66.7 psva still placed themselves in the latter group (Grigg and Stephens, 1999), while in 1997/1998, 51.1 psva of a university dental school in Ireland considered their expertise with computers as poor (Ray and Hannigan, 1999). The analysis of a decade of data collection at a U.S. medical school confirms the students' increasing computer skills over the study period.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The addition of an IT skills course could be beneficial to trainee doctors not only in medical, but also in the management sector. A survey in an Irish dental hospital showed that the lack of experience with computers may be addressed by including suitable computing courses at the secondary level and tertiary level education and such training may promote greater use of generic softwares, particularly in the library, with a more electronic-based approach to data handling (Ray and Hannigan, 1999). It has also been reported that medical students who have not acquired basic computer information technology skills by the third year of undergraduate training are unlikely to do so in the final hospital-based years and hence undergraduate curricula for medical students must incorporate specific computer training (Osman and Muir, 1994).…”
Section: Discussionmentioning
confidence: 99%